Coronary artery calcium and the competing long-term risk of cardiovascular vs. cancer mortality: the CAC Consortium. (24th December 2018) - Whelton, Seamus P; Al Rifai, Mahmoud; Dardari, Zeina; Shaw, Leslee J; Al-Mallah, Mouaz H; Matsushita, Kunihiro; Rumberger, John A; Berman, Daniel S; Budoff, Matthew J; Miedema, Michael D; Nasir, Khurram; Blaha, Michael J
Abstract: Aims: Coronary artery calcium (CAC) is the strongest predictor of cardiovascular disease (CVD), yet is also associated with chronic non-CVD such as cancer. We performed this analysis in order to describe the association of CAC with CVD vs. cancer mortality. Methods and results: The CAC Consortium is comprised of 66 636 scans performed in asymptomatic patients without known CVD. The mean age was 54 ± 11 years and 67% of participants were men. Cause of death was ascertained from death certificates. The association of CAC with cause-specific mortality was calculated using Fine and Gray sub-distribution hazard ratio (SHR) models, which account for competing causes of death. There were 3158 deaths over a median 12 ± 4 years follow-up (37% cancer and 32% CVD). Cancer was the leading cause of death when CAC = 0 (50%) with CVD overtaking cancer when baseline CAC >300. Compared to participants with CAC = 0, the SHR for CVD mortality was 1.44 [95% confidence interval (CI) 1.14–1.81], 2.26 (95% CI 1.76–2.90), and 3.68 (95% CI 2.90–4.67) for patients with CAC 1–99, 100–299, and ≥300, and the SHR for cancer was 1.04 (95% CI 0.88–1.23), 1.19 (95% CI 0.98–1.46), and 1.30 (95% CI 1.07–1.58). Conclusion: Cancer was the leading cause of death for patients with baseline CAC = 0, whereas CVD overtook cancer above a threshold of CAC >300. These results argue for a focused approach for patients at the extremes of CAC scoring while suggesting that combined CVD and cancer primary prevention strategies for patients with intermediate CAC scores may significantly decrease mortality from the two leading causes of death.